Crystalloid body, refractile body and virus-like particles in Apicomplexa: what is in there? - Lemgruber, Leandro; Lupetti, Pietro (Parasitology, 2012)
The phylum of Apicomplexa comprises parasitic protozoa that share distinctive features such as the apical complex, the apicoplast, specialized cytoskeletal components and secretory organelles. Other unique cytoplasmic inclusions sharing similar features have been described in some representatives of Apicomplexa, although under different denominations. These are the crystalloid body, present for example in Cryptosporidium, Plasmodium and Cystoisospora; the refractile body in Eimeria and Lankesterella; and virus-like particles, also present in Eimeria and Cryptosporidium. Yet, the specific role of these cytoplasmic inclusions in the cell cycle of these protozoa is still unknown. Here, we discuss their morphology, possible inter-relatedness and speculate upon their function to bring these organelles back to the attention of the scientific community and promote new interest towards original research on these elusive structures.